Microphthalmia-associated transcription factor expression levels in melanoma cells contribute to cell invasion and proliferation - Vachtenheim, Jiri; Ondrušová, Lubica (Experimental dermatology, 2015)
Microphthalmia-associated transcription factor (MITF) is a nodal point in melanoma transcriptional network that regulates dozens of genes with critical functions in cell differentiation, proliferation and survival. Highly variable MITF expression levels exist in tumor cell subpopulations conferring marked heterogeneity and plasticity in the tumor tissue. A model has been postulated whereby lower MITF levels favour cell invasion and suppress proliferation, whereas high levels stimulate differentiation and proliferation. Additionally, MITF is considered to be a prosurvival gene and a lineage addiction oncogene in melanoma. Herein, we review how MITF expression may affect the melanoma phenotype with consequences on the survival, invasion and metastasis of melanoma cells, and we discuss the research challenges.
Keywords: exprese genu; nádorové mikroprostředí; Gene Expression; Protein Stability; viabilita buněk; MicroRNAs; BRN2; SOX2; stabilita proteinů; Cell Proliferation; Epithelial-Mesenchymal Transition; Skin Neoplasms; mikro RNA; GLI2; Neoplasm Invasiveness; Cell Survival; jaderné proteiny; faktory domény POU; Models, Biological; MAP kinasový signální systém; transkripční faktory Krüppel-like; Melanoma; MAP Kinase Signaling System; RNA nádorová; lidé; microphthalmia-associated transcription factor; biologické modely; RNA, Neoplasm; transkripční faktory SOXB1; Humans; melanoma; invazivní růst nádoru; protein Gli2 s motivem zinkových prstů; POU Domain Factors; Zinc Finger Protein Gli2; Kruppel-Like Transcription Factors; apoptóza; proliferace buněk; Microphthalmia-Associated Transcription Factor; nádory kůže; SOXB1 Transcription Factors; Homeodomain Proteins; Tumor Microenvironment; melanom; transkripční faktor spojený s mikroftalmií; homeodoménové proteiny; Nuclear Proteins; epitelo-mezenchymální tranzice; Apoptosis